Pengaruh pengawasan preventif, pengawasan detektif dan penganggaran berbasis kinerja terhadap efektifitas pengendalian anggaran (studi empiris pada skpd kabupaten kuantan singingi) - Hendrawan, Jaka; ', Kamaliah; ', Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to look at the Effects of Preventive Monitoring, Surveillance Detective and Effectiveness Against Performance-Based Budgeting on Budgetary Control of the Regency Kuantan Singingi. The population in this study are all compulsory service Performance Accountability Report Government Agencies in the County Government Kuantan Singingi, Riau province, amounting to 29 offices. While the sample is employees who participate in the budgetary participation Kuantan Singingi District Government as a whole, amounting to 93 people. To test the hypothesis of the study used multiple regression analysis method with the help of SPSS software. The results show that preventive control does not significantly influence the effectiveness of budgetary control. While the detective monitoring and performance-based budgeting significantly influence the effectiveness of budgetary control with empirical studies on Kuantan Singingi district offices. Donations effect of preventive monitoring, supervision and performance-based budgeting detective on the effectiveness of budgetary control with empirical studies in the Kuantan district offices Singingi by 52.9%.Keywords: Effect of Preventive Monitoring, Surveillance Detective, Performance Based Budgeting and Budgetary Control Effectiveness.